KERJASAMA INDONESIA-KANADA DALAM UPAYA PENGENTASAN KEMISKINAN DI SULAWESI TAHUN 2010-2014 - Maria Clara Panjaitan; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study is a qualitative research by conducting literature review and also compiling data from journal, books and website. This study aims to describes about the cooperation between Indonesia and Kanada due to decrease poverty in Sulawesi through BASICS-CIDA Project on 2010-2014 period.This research uses a liberalism perspective. Liberalism is set on the idea that actors in international system could reach a peaceful world order by doing cooperation or partnership. While the theory is international cooperation, in international cooperation told that the country or the participant of cooperation will get some gain and the problems in both countries can be solved easily. In this study the problem in Indonesia which is poverty can be solved by doing cooperation with Kanada.By this research the writer finds out that through BASICS-CIDA Project, the poverty in Sulawesi especially in North Sulawesi and Southeast Sulawesi can be solved gradually though the process take much longer time.Keywords: BASICS-CIDA, Poverty, Education, Health, Sulawesi.